PERANAN KELOMPOK TANI DALAM MENINGKATKAN PENDAPATAN USAHATANI PADI SAWAH LAHAN PASANG SURUT DI DESA SUNGAI RENGAS KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Wiwi Indahsari; Abdul Hamid A. Yusra; Novira Kusrini (Fakultas Pertanian Universitas Tanjungpura, 2020)
This study aims to analyze the role of farmer group increasing the income of tidal paddy farming in Sungai Rengas Village, Sungai Kakap Subdistrict, Kubu Raya Regency. The research method used was a survey method, the location of this research was chosen deliberately namely in the village of Rengas River. With the consideration that the rengas river village has an organized and active farmer group and has the potensial to develop tidal rice farming which is included in the overflow type B. The average income of tidal rice farmer in respondent farming season oktober to February 2019 was Rp.8.159.116 , with an average production of 2.274 kg/mt, for income per hectare was Rp. 9.065.684.The results of the analysis of the SPSS (Crosstab) cross tabulation test the relationship of the role of farmer groups to the income of tidal paddy farmers produce the role of farmer groups are in the low to high category and are dominated in the category by 81.4%, farm income is in the low to high category and dominated by income is in high category by 39.5%. this shows that a high role will also generate high income.Key words: Farmer groups, tidal land, income